Insurance distribution and customer protection in the frame of the European international civil procedural law: Una visión desde la perspectiva del derecho procesal civil internacional europeo - Aguilar Grieder, Hilda (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
This study analyzes one of the most complex legal sectors of the international contract law: the insurance contracts. In the insurance field there is a wide variety of contracts. In particular, this paper analyses the specific degree of protection of the insured or policyholder in the field of international jurisdiction. The issue is studied from both a lege ferenda and a lege lata perspective.
Keywords: European International Civil Procedural Law; international jurisdiction; international agreements; distribution of insurance; international insurance contracts; insured protection level